Pengunaan Model Pembelajaran Kooperatif Tipe Make A Match Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPS Siswa Kelas V Di SDN Tlogomas 2 Kota Malang - FIRSTA BAGUS SUGIHARTO; CHUSNUL CHOTIMAH; VERONIKA ICA (Universitas Insan Budi Utomo, 2024)
The use of the Make A Match cooperative learning model to improve student learning outcomes in social studies subjects for fifth-grade students at Tlogomas 2 Elementary School, Malang City, elementary school, teacher education study program, faculty of education at Tribhuwana Tunggadewi University, supervised by Dr. Firsta Bagus Sugiharto, S.Pd., M.Pd and Chusnul Chotimah, S.Pd., M.Pd. The purpose of this study was to describe the application of the Make A Match type of cooperative learning model to improve social studies learning outcomes for fifth-grade students at SDN Tlogomas 2 Malang City. This study used a class action research method (CAR) with a qualitative descriptive approach which consisted of 2 cycles, Cycle I and Cycle II, cycle I was held in 2 meetings, and cycle II was also held in 2 meeting, each cycle consisting of 4 stages namely, planning, implementing, observing data collection techniques in this study using the method of observation, interviews, learning achievement tests, and documentation. The results showed that: (1) the application of the Make A Match type of cooperative learning model in cycle I meeting I, 62,5% in the less category and meeting II, 75% in the sufficient categories, in the implementation of cycle II meeting I the percentage was 87.5% in the category very good, the second meeting, 93.75% with excellent category. (2) increasing social studies learning outcomes by using the Make A Match type cooperative learning model for social studies subjects in cycle I meeting I. 46% with an average value of 72.70% than in the second cycle experienced an increase in the first meeting the percentage of completeness was 76.92% with an average value of 81.15% and at the second meeting the percentage of completeness was 84.61% with the average value is 86.92%, therefore it can be concluded that the use of the Make A Match cooperative learning model to improve social studies learning outcomes for fifth-grade students at SDN Tlogomas 2 Malang City